COMPARATIVE CHARACTERISTICS OF MORPHOMETRIC CHANGES IN THE KIDNEYS DURING CHEMICAL BURNS OF THE DIGESTIVE ORGANS (Modern education and development, 2024)
Comparative characteristics of morphometric changes in the kidneys during chemical burns is the main factor in their diagnosis and treatment and allows in this case to cure the patient completely without complications. Therefore, if scientific research is carried out in this direction, the life expectancy of most patients will increase and their health will improve.